Prospective Study on Determination of Optimal Drainage Volume in Massive Pleural Effusion Based on Pleural Effusion Index - Jeff Lapian; Adrian Tangkilisan; Wega Sukanto; Christha Tamburian; Fredrik G. Langi (e-CliniC, 2022)
Abstract: Clinical manifestations of pleural effusion are influenced by the fluid volume and the underlying disease. Pleural effusion index (PEI) is the ratio between the maximum width of pleural effusion and maximum width of hemithorax in patient with lateral decubitus position. However, PEI as the indicator of pleural effusion volume is rarely used. This study aimed to determine the optimal drainage volume of massive pleural effusion based on initial PEI value. This was an observational study with a hospital-based prospective cohort design conducted at Prof. Dr. R. D. Kandou Hospital in Manado, Indonesia. Samples were patients presented with massive pleural effusion. This study analyzed the details of thoracentesis, demographic profile, past medical history, clinical charac-teristics, laboratory findings, postoperative observations, admission and discharge time. The results obtained 32 patients with massive pleural effusion, consisting of 17 males (53%) and 15 females (47 %). The average respirations of pre-drainage and delta-drainage patients were 27 times per minute and 24 times per minute respectively while the standard deviations were slightly different. The median respiratory rate of post-drainage was 24 times per minute. In conclusion, measurement of PEI in pre-drainage patients had significant correlation in determining the optimal drainage volume.Keywords:Â pleural effusion; pleural effusion indexÂ Abstrak: Manifestasi klinis efusi pleura dipengaruhi oleh volume cairan dan penyakit yang mendasarinya. Pleural effusion index (PEI) adalah perbandingan antara lebar maksimum efusi pleura dan lebar maksimum hemitoraks pada pasien dengan posisi lateral dekubitus, namun PEI sebagai indikator volume efusi pleura jarang digunakan. Penelitian ini bertujuan untuk menentukan volume drainase optimal efusi pleura masif berdasarkan nilai PEI awal. Jenis penelitian ialah studi observasional dengan desain kohort prospektif berbasis rumah sakit di Prof. Dr. R. D. Rumah Sakit Kandou Manado, Indonesia. Sampel penelitian ialah pasien dengan efusi pleura masif. Pada penelitian ini dianalisis rincian torakosentesis, profil demografis, riwayat penyakit terdahulu, karakteristik klinis, hasil laboratorium, pengamatan pasca operasi, waktu masuk dan keluar. Penelitian ini melibatkan 32 pasien terdiri dari 17 laki-laki (53%) dan 15 perempuan (47%). Respirasi rerata pasien pra-drainase dan delta-drainase masing-masing 27 kali per menit dan 24 kali per menit sedangkan standar deviasinya hanya sedikit berbeda. Tingkat pernapasan rerata pasca drainase ialah 24 kali per menit. Simpulan penelitian ini ialah pengukuran PEI pada pasien pra drainase memiliki korelasi bermakna dalam menentukan volume drainase yang optimal.Kata kunci: efusi pleura; pleural effusion index